2010
DOI: 10.1002/j.2050-0416.2010.tb00423.x
|View full text |Cite
|
Sign up to set email alerts
|

Note - Preliminary Applications of Response Surface Modelling to the Evaluation of Optimal Growth Conditions for Beer-spoiling Pediococcus damnosus

Abstract: Beer‐spoiling lactic acid bacteria (LAB) belong to the most harmful contaminants in the brewing industry and various rapid molecular detection methods have been introduced for the detection of these organisms. However, the enrichment cultivation steps needed prior to detection by molecular methods can extend the duration of the analytical procedure by up to several days. The use of brewery‐specific enrichment cultivation media has been recommended due to the large variety within the group of LAB, as well as di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0
2

Year Published

2011
2011
2016
2016

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 16 publications
2
2
0
2
Order By: Relevance
“…Initial medium is B-MRS with reduced concentrations of all the components and a lower pH (Taskila et al, 2010b). The medium allows the growth of all pediococci used in the study and a wide range of lactobacilli (95.3%), which is consistent with the results of Taskila et al (2010b).…”
Section: Růst Mléčných Bakterií V Tekutých Médiíchsupporting
confidence: 67%
See 3 more Smart Citations
“…Initial medium is B-MRS with reduced concentrations of all the components and a lower pH (Taskila et al, 2010b). The medium allows the growth of all pediococci used in the study and a wide range of lactobacilli (95.3%), which is consistent with the results of Taskila et al (2010b).…”
Section: Růst Mléčných Bakterií V Tekutých Médiíchsupporting
confidence: 67%
“…Výchozí půdou je B-MRS se sníženými koncentracemi všech složek a nižším pH (Taskila et al 2010b). Na půdě rostou všechny pediokoky použité ve studii a široké spektrum laktobacilů (95,3 %), což je v souladu s výsledky studie Taskily et al (2010b).…”
Section: Colonies Of Lactobacillus Brevis Ribm 2-111 After 5 Days Of unclassified
See 2 more Smart Citations
“…Suzuki and coworkers 80 showed that the resuscitation of slowly growing beer spoilers, such as L. lindneri, can be remarkably faster at a low glucose concentration compared to commonly used 10-20 g/L. Similar findings were found in our study 92 , indicating that the use of a lower initial concentration of glucose in MRS could be advantageous in the case of beer samples. The nutrient supply can be arranged either by manual addition of nutrients after a short adaptation phase or by use of slow release techniques.…”
Section: Environmental Stress Factorssupporting
confidence: 89%